"Worth(less) papers" : are journal impact factor and number of citations suitable indicators to evaluate quality of scientists? - Racz, Aleksandar (Array, 2018)
Technology driven changings with consecutive increase in the on-line availability and accessibility of journals and papers rapidly changes patterns of academic communication and publishing. The dissemination of important research findings through the academic and scientific community begins with publication in peer-reviewed journals. Aim of this article is to identify, critically evaluate and integrate the findings of relevant, high-quality individual studies addressing the trends of enhancement of visibility and accessibility of academic publishing in digital era. The number of citations a paper receives is often used as a measure of its impact and by extension, of its quality. Many aberrations of the citation practices have been reported in the attempt to increase impact of someone’s paper through manipulation with self-citation, inter-citation and citation cartels. Authors revenues to legally extend visibility, awareness and accessibility of their research outputs with uprising in citation and amplifying measurable personal scientist impact has strongly been enhanced by on line communication tools like networking (LinkedIn, Research Gate, Academia.edu, Google Scholar), sharing (Facebook, Blogs, Twitter, Google Plus) media sharing (Slide Share), data sharing (Dryad Digital Repository, Mendeley database, PubMed, PubChem), code sharing, impact tracking. Publishing in Open Access journals. Many studies and review articles in last decade have examined whether open access articles receive more citations than equivalent subscription toll access) articles and most of them lead to conclusion that there might be high probability that open access articles have the open access citation advantage over generally equivalent payfor-access articles in many, if not most disciplines.